Optimization of Material Requirement Planning Using A Linear Program - Nurhajizah, Nurhajizah; Rakhmawati, Fibri; Sutarman, Sutarman (International Conference on Sciences Development and Technology, 2022)
This study discusses the optimization of the production cost of dodol using Material Requirement Planning (MRP) with a linear programming to solve the problem of optimizing production costs in the dodol pulut sari business. This study identifies the MRP model, determines the objective and constraint functions of the MRP model, then optimizes the MRP model into a linear programming using the simplex method. There are various constraint function encountered in the company by modeling them into MRP, namely the main raw materials such as pulut, sugar, coconut milk, vanilla, management time, and waiting time for orders. While the objective function is to minimize production costs. The results of the MRP optimization study with a linear programming obtained Rp. 10.368.000 and has a difference with the costs incurred by the company of Rp. 80.000. therefore, the production cost of the MRP model by optimizing the linear programming using the simplex method is more efficient and can be used to solve problems in minimizing production costs.